Single-cell RNA-seq unravels alterations of the human spermatogonial stem cell compartment in patients with impaired spermatogenesis - Sara Di Persio (Cell Reports Medicine, 2021)
Summary: Despite the high incidence of male infertility, only 30% of infertile men receive a causative diagnosis. To explore the regulatory mechanisms governing human germ cell function in normal and impaired spermatogenesis (crypto), we performed single-cell RNA sequencing (>30,000 cells). We find major alterations in the crypto spermatogonial compartment with increased numbers of the most undifferentiated spermatogonia (PIWIL4+). We also observe a transcriptional switch within the spermatogonial compartment driven by increased and prolonged expression of the transcription factor EGR4. Intriguingly, the EGR4-regulated chromatin-associated transcriptional repressor UTF1 is downregulated at transcriptional and protein levels. This is associated with changes in spermatogonial chromatin structure and fewer Adark spermatogonia, characterized by tightly compacted chromatin and serving as reserve stem cells. These findings suggest that crypto patients are disadvantaged, as fewer cells safeguard their germline’s genetic integrity. These identified spermatogonial regulators will be highly interesting targets to uncover genetic causes of male infertility.